For Church or People: The History of Land Dispute in Sikka Regency, East Nusa Tenggara Province from the Perspective of Tana' Ai Community - Desmiwati Desmiwati; Suraya Afiff; Edwin Martin; Surati Surati; Kresno Agus Hendarto; Rini Astuti (Forest and Society)
This study employs a political ecology approach to analyze the dynamics of land ownership in Indonesia, focusing on the Tana' Ai community in Sikka Regency, East Nusa Tenggara province. We argue that agrarian change is driven by external actors, including private companies that religious institutions and government agencies own. The latter often impose their will on indigenous populations, which can result in land conflicts, marginalization, and uneven capital accumulation. In particular, the church's status as a land use permit holder from the colonial era complicates the Tana' Ai ethnic community's ability to assert its ancestral land rights. To understand this further, this study examines the interactions between the church, local communities, and the state in land management and their impact on the dynamics of power and resistance of ethnic Tana' Ai communities to social and policy change. We ask, is land managed by the community or the church? The research contributes to the growing body of literature. It fills a significant gap on land disputes in Indonesia, which also appear to be conducted by religious institutions, and the long-term impacts of such conflicts on indigenous societies. We used qualitative methods, including interviews, participant observation, and archival analysis, across 3 villages in Sikka Regency. This understanding is crucial for addressing the socio-political and cultural challenges the Tana' Ai community faces in reclaiming their land rights and ensuring their sustainable livelihoods.